BEOL process integration technology for 45 nm node porous low-k/copper interconnects - Matsunaga, N.; Nakamura, N.; Higashi, K.; Yamaguchi, H.; Watanabe, T.; Akiyama, K.; Nakao, S.; Fujita, K.; Miyajima, H.; Omoto, S.; Sakata, A.; Katata, T.; et al. (Proceedings of the IEEE 2005 International Interconnect Technology Conference, 2005, 2005)
Highly reliable BEOL integration technology with porous low-k (k=2.3) was realized by development focusing on plasma damage control and moisture control. A hybrid dielectric scheme with damage resistant porous low-k films and buffer film was applied in view of its inherent advantages for realizing reliable porous low-k integration. A metallization process was developed from the viewpoint of suppressing morphology and adhesion degradation of barrier metal by oxidation. A dummy wiring pattern was also adopted to remove moisture absorbed in porous low-k films. Stress-migration and electromigration satisfying practical reliability were obtained with via size of 75 nm for the first time by utilizing all possible measures for reducing the damage and the moisture.